Establishing a Person-centred Framework of Self-identity After Traumatic Brain Injury: A Grounded Theory Study to Inform Measure Development - Levack, WM; Boland, P; Taylor, WJ; Siegert, RJ; Kayes, NM; Fadyl, Joanna; McPherson, KM (BMJ Publishing Group Ltd., 2014)
Objective To develop a theoretically sound, client-derived framework to underpin development of a measure reflecting the impact of traumatic brain injury (TBI) on a person's self-identity. Design Grounded theory, based on transcription of audio recordings from focus group meetings with people who have experienced TBI, analysed with constant comparative methods. Setting 8 different urban and rural communities in New Zealand. Participants 49 people (34 men, 15 women), 6 months to 36 years after mild-to-severe TBI. Results The central concept emerging from the data was that of desiring to be or having lost a sense of being an integrated and valued person. The three main subthemes were: (1) having a coherent, satisfying and complete sense of oneself, (2) respect, validation and acceptance by others and (3) having a valued place in the world. Conclusions This study reinforces the notion that change in self-identity is an important aspect of life after TBI, and provides information on what this concept means to people with TBI. In order to scientifically evaluate relationships between self-identity and other aspects of health (eg, depression, quality of life), and to test the effect of interventions to address problems with self-identity after TBI, a quantitative tool for evaluation of this construct is required. Themes from this research provide a foundation for the development of a measure of self-identity grounded in the language and experience of people with TBI.
Keywords: Lived experience; Outcome; Qualitative research; Self-concept; Self-identity; Traumatic brain injury